2017
DOI: 10.1371/journal.pone.0171259
|View full text |Cite
|
Sign up to set email alerts
|

Cell reproductive patterns in the green alga Pseudokirchneriella subcapitata (=Selenastrum capricornutum) and their variations under exposure to the typical toxicants potassium dichromate and 3,5-DCP

Abstract: Pseudokirchneriella subcapitata is a sickle-shaped freshwater green microalga that is normally found in unicellular form. Currently, it is the best known and most frequently used species of ecotoxicological bioindicator because of its high growth rate and sensitivity to toxicants. However, despite this organism’s, our knowledge of its cell biology—for example, the patterns of nuclear and cytoplasmic division in the mitotic stage—is limited. Although it has been reported that P. subcapitata proliferates by popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…The toxic effects of potassium dichromate on the photosynthesis were also investigated in five species of marine microalgae, and showed an overall sensitivity and decrease of the photosynthesis efficiency with increased time and concentration . Additionally, increasing concentration of potassium dichromate has shown to be inducing a general decline in cell densities in the green alga Pseudokirchneriella subcapitata . Moreover, recent study by Wang et al on the effect of copper on C. ehrenbergii showed that F v /F m was considerably affected by copper toxicity and also declined with increasing copper concentration and exposure time, indicating that chlorophyll content and/or photosynthetic electron transport might be inhibited by exposure to the metal …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic effects of potassium dichromate on the photosynthesis were also investigated in five species of marine microalgae, and showed an overall sensitivity and decrease of the photosynthesis efficiency with increased time and concentration . Additionally, increasing concentration of potassium dichromate has shown to be inducing a general decline in cell densities in the green alga Pseudokirchneriella subcapitata . Moreover, recent study by Wang et al on the effect of copper on C. ehrenbergii showed that F v /F m was considerably affected by copper toxicity and also declined with increasing copper concentration and exposure time, indicating that chlorophyll content and/or photosynthetic electron transport might be inhibited by exposure to the metal …”
Section: Resultsmentioning
confidence: 99%
“…73 Additionally, increasing concentration of potassium dichromate has shown to be inducing a general decline in cell densities in the green alga Pseudokirchneriella subcapitata. 74 Moreover, showed that F v /F m was considerably affected by copper toxicity and also declined with increasing copper concentration and exposure time, indicating that chlorophyll content and/or photosynthetic electron transport might be inhibited by exposure to the metal. 35…”
Section: Photosynthesis Efficiency and Ros In Metaltreated Cellsmentioning
confidence: 98%
“…Selenastrum capricornutum , Pseudokirchneriella subcapitata and Raphidocelis subcapitata are the same species named in different periods [ 25 ]. The species is a sickle-shaped and unicellular green microalga that is normally found in fresh water.…”
Section: Introductionmentioning
confidence: 99%
“…In the Sphaeropleales cell cycle, the stage with motility (e.g. flagellates) is not dominant or not known 60 , 61 . Immobility may force cells to adapt to different environmental conditions aided by their numerous transporters.…”
Section: Resultsmentioning
confidence: 99%